Analisis Hukum Terhadap Pelaku Tindak Pidana Pencurian Peralatan Base Transceiver Station Pemancar Signal Tower - Harahap, Igor Ivannov; Nadirah, Ida (Universitas Muhammadiyah Sumatera Utara, 2024)
The crime of theft of tower signal transmitter base transceiver station equipment is a crime of theft in which the object stolen is equipment for transmitting signals for cellphones, wifi, and electronic devices that use other signals. In Article 362 of the Criminal Code, theft is anyone who Anyone who takes something, which wholly or partly belongs to another person, with the intention of possessing it unlawfully, is threatened with theft, with a maximum imprisonment of five years or a maximum fine of nine hundred million rupiah. In this article it is regulated to ensnare perpetrators of criminal acts of theft. The research method used is normative juridical research, namely legal research carried out by examining library materials or secondary data. Criminal law enforcement is part of criminal policy as one of the overall crime prevention policies. Indeed, criminal law enforcement is not the only thing that can be a hope for being able to resolve or deal with crime completely, but its presence is highly expected in Indonesia which is based on law. to enforce criminal law in Indonesia. Law enforcement is aimed at increasing order and legal certainty in social life. This is done to regulate the functions, duties and authority of institutions that have the task of enforcing the law